LATE GLACIAL AND HOLOCENE ENVIRONMENTAL CHANGE INFERRED FROM THE PÁRAMO OF CAJANUMA IN THE PODOCARPUS NATIONAL PARK, SOUTHERN ECUADOR (2014)
To reconstruct the environmental history including vegetation, fire and climate dynamics, from the Cajanuma valley area (3285 m elevation) in the Podocarpus National Park, southern Ecuador, we address the following major research question: (1) How did the mountain vegetation developed during the late Glacial and Holocene? (2) Did fire played an important control on the vegetation change and was it natural or of anthropogenic origin?. Palaeoenvironmental changes were investigated using multiple proxies such as pollen, spores, charcoal analyses and radiocarbon dating. Pollen data highlight that during the late Glacial and transition to the early Holocene (ca. 16 000–10 500 cal yr BP) herb páramo was the main vegetation type around the study area, while subpáramo and mountain rainforest were low represented. The early and mid-Holocene (ca. 10 500 to 5600 cal yr BP) is marked by high abundance of páramo during the early Holocene followed by a slight expansion of mountain forest during the mid-Holocene. During the mid- to late Holocene (ca. 5600–1200 cal yr BP) there is a significant presence of páramo and subpáramo while Lower Mountain Forest decreased substantially. Though, Upper Mountain Forest remained relatively stable during this period. The late Holocene, from ca. 1200 cal yr BP to present, was characterized by páramo; although, mountain forest and subpáramo presented significantly abundance compared to the previous periods. Fires became frequent since the late Holocene. The marked increased local and regional fire intensity during the wetter late Holocene strongly suggests that were of anthropogenic origin. During the late Glacial and early Holocene, the upper forest line was located at low elevations; but shifted slightly upslope to higher elevations during the mid-Holocene.